Niche-localized tumor cells are protected from HER2-targeted therapy via upregulation of an anti-apoptotic program in vivo - Jason J. Zoeller (Nature Portfolio, 2017)
Drug resistance: Overcoming localized resistance to anti-HER2 therapy Location-specific subpopulations of breast cancer cells adapt to targeted drug treatment, but therapeutic strategies exist to attack these niche-protected cells. A team led by Joan Brugge and Jason Zoeller from Harvard Medical School, USA, implanted human HER2+ breast tumor cells into the ducts of mouse mammary glands to recapitulate the architecture of ductal carcinoma in situ, a common type of non-invasive breast cancer. They found that cancer cells located on the outer rim of the tumors were resistant to lapatinib, a drug that targets the HER2 protein. Combination treatment with lapatinib and a drug that blocks a pro-survival protein called BCL2 that was specifically enriched in the outer cells after lapatinib treatment helped kill more cells. Complete elimination of the resistant cells was achieved with an antibody-drug conjugate, T-DM1, that binds to HER2 and then releases a chemotherapeutic payload.